1997
DOI: 10.1039/a702492d
|View full text |Cite
|
Sign up to set email alerts
|

Guest–guest interactions in urea inclusion compounds †

Abstract: Different types of urea inclusion compounds have been studied to test the importance of the molecular interactions between the guests. Experimental evidence has been obtained from the EPR spectra of radicals derived from guests by room temperature -ray irradiation of the inclusion compounds. The guest-guest intra-channel interactions are very important in the case of tridecanedioic and tetradecanedioic dicarboxylic acid guests which give rise to strong intermolecular hydrogen bonding between the carboxylic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The dynamics of included polymers and elongated molecules forming high-melting nanocomposites is particularly intriguing and promotes anisotropic motions and mesophases . EPR spectroscopies have been applied to stable nitroxide radicals included as guests in zeolites, to radicals and macroradicals formed by ionizing radiation in zeolites, and in organic hosts such as urea and PHTP . Radicals as probes have also been produced by photolysis .…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of included polymers and elongated molecules forming high-melting nanocomposites is particularly intriguing and promotes anisotropic motions and mesophases . EPR spectroscopies have been applied to stable nitroxide radicals included as guests in zeolites, to radicals and macroradicals formed by ionizing radiation in zeolites, and in organic hosts such as urea and PHTP . Radicals as probes have also been produced by photolysis .…”
Section: Introductionmentioning
confidence: 99%
“…1 Moreover, the supramolecular organization and the topological constraints give rise to a different conformational and motional behavior of the guests. [2][3][4] In this paper we report a study on the photoexcited triplets of three nitro substituted diphenylpolyenes in IC and in glassy and polymeric matrices.…”
Section: Introductionmentioning
confidence: 99%
“…This has been shown by studying a series of UIC in which the guest species is a mixture with different concentrations of 10-NDO and nonadecane. 8 The radical is formed on the ketone molecules only, and it is found that the EPR linewidths are smaller and the radical motion faster when the composition of the guest mixture is richer in nonadecane. All the other experimental settings being the same, this result implies that the motion of the 10-NDO radical is affected by the type of molecules occupying the adjacent channels.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, we have recently studied UIC with several types of functionalized alkanes as guest molecules by EPR and ENDOR spectroscopy. [5][6][7][8] Single crystals of the desired compound were produced and then γ-irradiated. Stable radicals are produced only on the guest molecules by cleavage of a C-H bond near the functional group.…”
Section: Introductionmentioning
confidence: 99%